Polish pseudo-words list: dataset of 3023 stimuli with competent judges’ ratings - Imbir, Kamil K.; Spustek, Tomasz; Żygierewicz, Jarosław (Frontiers in Psychology, 2015)
Pseudo-words are stimuli, which are useful in research concerning lexical processing. As in the case of existing words, they are language dependent; thus, they should be generated for each language separately. The Polish Pseudo-words List (PPwL) is a dataset presenting a set of 3023 stimuli (words of 4–13 letters long). They were generated using an algorithm substituting random letters in existing words with respect to the frequency of letters in certain positions. We put out the raw set for a competent judges’ assessment and included the responses in the dataset. PPwL allows the choice of suitable control stimuli for experiments concerning lexical processing.